2021
DOI: 10.1002/dvdy.387
|View full text |Cite
|
Sign up to set email alerts
|

BMP signaling and skeletal development in fibrodysplasia ossificans progressiva (FOP)

Abstract: FOP is caused by dysregulated BMP pathway activity that alters bone formation, both through induction of extra-skeletal (heterotopic) ossification and through skeletal developmental defects.• The endogenous skeleton of individuals with FOP is affected, particularly at the joints, at multiple sites throughout the body.• The developmental skeletal phenotype of FOP shows similarities to other models of altered BMP pathway signaling, providing insight into the causative molecular mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 116 publications
(324 reference statements)
0
12
0
1
Order By: Relevance
“…BMP signaling is required for various activities during early development, including cell proliferation, apoptosis, and differentiation [ 15 ]. BMPs also serve a critical role in maintaining adult tissue homeostasis, including preservation, vascular remodeling, and the fracture repair [ 53 ]. Any deficit in their production or function mostly results in a visible abnormalities or severe diseases in the tissues [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…BMP signaling is required for various activities during early development, including cell proliferation, apoptosis, and differentiation [ 15 ]. BMPs also serve a critical role in maintaining adult tissue homeostasis, including preservation, vascular remodeling, and the fracture repair [ 53 ]. Any deficit in their production or function mostly results in a visible abnormalities or severe diseases in the tissues [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The skeletal abnormalities found in patients with p.Arg258Gly ACVR1 were atypical and more severe than those reported in classical FOP patients and other atypical FOP patients in the following points: (1) heterotopic ossification occurred at an earlier age and was more frequent and (2) the feet and hands were both affected, presenting with short fingers and toes and lack of nails [ 7 ]. Through ACVR1, BMP signaling contributes to not only ossification but also large and small joint formation [ 1 , 9 ]. In FOP with pathogenic ACVR1 variants, abnormally increased BMP signaling causes heterotopic ossification, joint dysplasia, growth plate dysplasia, and osteochondroma formation.…”
Section: Discussionmentioning
confidence: 99%
“…Other reports showed that during development components of the FGF, Wnt, Notch, BPM, and Hedgehog signaling orchestrate crucial cellular events including proliferation, migration, differentiation, epithelial-mesenchymal transition (EMT), morphogenesis and somite myogenesis patterning. When gene expression controlling these events is dysregulated, it leads to disease induction ( Hansson et al, 2004 ; Logan and Nusse, 2004 ; Ma et al, 2010 ; Teven et al, 2014 ; Xiao et al, 2017 ; Abreu de Oliveira et al, 2022 ; Alrefaei and Abu-Elmagd, 2022 ; Towler and Shore, 2022 ). Although our RT did not receive microRNA-related manuscripts, it is well-established that microRNAs play an important role in physiology and disease ( Sayed and Abdellatif, 2011 ; Bhaskaran and Mohan, 2014 ; Kalayinia et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%